On the Use of the Theory of Probability in Economics - Weckstein, R. S. (Review of Economic Studies, 1952)
Journal Article On the Use of the Theory of Probability in Economics Get access R. S. Weckstein R. S. Weckstein New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 3, 1952, Pages 191–198, https://doi.org/10.2307/2295889 Published: 01 January 1952